Monitoring, Reclamation and Management of Salt-Affected Lands (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Salt-affected soils are present in nearly every irrigated area of the world and also occur in non-irrigated croplands and rangelands. Thus, virtually no land is immune to salinization. Therefore, to sustain life on earth, it is vital and urgent to control these problems and find innovative and comprehensive ways to use these extensive salt-affected soils and marginal water resources, at least for agricultural purposes. Reclamation, or simply the minimization of the effect of salinity and/or sodicity, is important. In this respect, the proper use of water for both plant growth, soil salinity, and sodicity control is probably of the greatest importance. Most of the existing literature concentrates on water and salt regimes and processes at field scale, but few explore soil carbon and nutrient cycling, which has aroused considerable debate over how to translate water and salt regime regulation into sustainable utilization and development in saline–alkaline land.